Menjaga Tradisi: Transformasi dan Keberlanjutan Rumah Tradisional di Era Kontemporer - Mustaqim, Ajril; Humaeni, Ayatullah (CV. Kurnia Grup, 2025)
Traditional houses represent a cultural identity rich in local values and ecological wisdom. However, in the midst of modernisation, its existence faces various challenges, such as the pressure of urbanisation, changes in lifestyle, and the lack of understanding of the younger generation. This research aims to explore the physical transformation and function of traditional houses and their sustainability factors in the contemporary era. Using a qualitative method with a descriptive approach, the research was conducted through observation, interviews, and literature study. The results show that traditional houses retain their architectural authenticity despite experiencing adaptations to modern needs, such as the addition of new facilities. The most significant sustainability factors include the role of local communities, government policy support, and adaptation of relevant technology. Traditional houses are also important symbols in maintaining the community's collective memory and centres of social activity. To ensure their preservation, synergy between the community, government and academia is needed to create sustainable policies. By integrating traditional elements into modern designs, traditional houses can remain relevant without losing their cultural value.